DEVELOPING PERFORMANCE MEASURMENT MODEL FOR EDUCATIONAL IN HOSPITAL BASED ON BALANCED SCORE CARD (Universitas Negeri Semarang, 2015)
This study is aimed to: (1) identify performance measurement model hospitals as educational institutions that have been implemented (2) produce a design model of hospital performance measurement as an educational institution base on the balanced scorecard, (3) analyze the effectiveness of the performance of the developed measurement model. The research model and development is carried out in the Hospital Pulmonary dr. Ario Wirawan Salatiga. Subjects were apprenticeship program participants, apprenticeship supervisor and hospital employees. Qualitative and quantitative data were collected to be analyzed using descriptive statistics and accuracy test model. The results of research and development show that (1) model of hospital performance measurement as an educational institution that is used today is the Government Performance Accountability Report; (2) the result of the model that is based on the Balanced Scorecard performance measurement shows that the development of indicators of customer perspective is customer satisfaction, customer loyalty, relationship quality, trust and customer acquisition; the development of financial perspective is accountability, economic ratios, the ratio of the efficiency and effectiveness ratio; the development of internal business process perspective is quality assurance, quality of facilities - infrastructure, innovation, patient preference, outpatient visits and hospitalization and use of the bed; and the development of learning and growth perspective is the instructor competence, job satisfaction, organizational commitment, work motivation, employee retention and employee productivity (3) The effectiveness of the measurement model that is developed is ability to provide a comprehensive framework to describe the hospital's vision and mission as an educational institution.